(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2020)
Cognitive Linguistics postulates that we could identify the metaphoric schemes used in a language if we can track its expressions and group them according to their semantic value. Three general corpora of non-proverbial expressions in Galician, Portuguese and Spanish, not parallel but with definitions, allow us to search those related particularly with a specific sense of shame. Through this we have detected a group of simple schemes, which are repeated in mutual combination, and we confirm that they can be applied for all three languages, with the source domains Weight, Redness, High Temperature, Descending Movement, Animal Behaviour and Hiding (oneself) or Fleeing, as well as other schemata using body parts, specifically Face, Head, Ears, Eyes and Mouth. In a future proposed contribution, we shall deal with more languages and the opposite concept of impudence, incorporating the inverted schemata, allowing to formulate an archimetaphor as a general template including all the abovementioned schemata.